Prognostic factors for survival in patients with pT1 N+ or T2–3 N0 gastric cancer in Japan. Issue 7 (27th February 2017) - Tokunaga, M; Ito, S; Yoshikawa, T; Nunobe, S; Fukagawa, T; Misawa, K; Cho, H; Katai, H; Sano, T; Terashima, M
Abstract: Background: The outcome for pT1 N+ or pT2–3 N0 gastric cancer is favourable, but some patients suffer from recurrent disease. The aim of this study was to identify prognostic factors in patients with pT1 N+ or pT2–3 N0 gastric cancer. Methods: This was a multicentre, retrospective cohort study. All patients with pT1 N+ or pT2–3 N0 gastric cancer who underwent curative gastrectomy at five high-volume, specialized cancer centres in Japan between 2000 and 2008 were included. Demographic, clinical, surgical and pathological data were collected. Independent prognostic factors were identified using a Cox proportional hazards regression model. Results: Some 1442 patients were included. The 5-year overall survival rate for patients with pT1 N+ or pT2–3 N0 gastric cancer was 92·0 per cent. Multivariable analysis for overall survival identified age (hazard ratio (HR) 2·67, 95 per cent c.i. 2·09 to 3·43), sex (HR 0·57, 0·39 to 0·83) and clinical tumour depth (cT) (HR 1·45, 1·06 to 1·98) as independent prognostic factors. Conclusion: Survival of patients with pT1 N+ or pT2–3 N0 gastric cancer is good. Age 65 years or above, male sex and cT2-4 category are associated with worse overall survival. Abstract : Low recurrence and excellent survival